The Prevalence of Undiagnosed Presurgical Cognitive Impairment and Its Postsurgical Clinical Impact in Older Patients Undergoing Lumbar Spine Surgery - Lee, Young-Seok (J Korean Neurosurg Soc, 2016)
OBJECTIVE: Because elderly patients are undergoing more surgeries, the importance of postoperative cognitive impairment (CI) evaluations is rising, especially for spine surgery, which is related to subjective pain. We investigated the prevalence of undiagnosed CI among elderly patients who underwent spine surgery and the impact of CI on postoperative outcomes. METHODS: The preoperative cognitive statuses of 129 patients over 65 who underwent lumbar spine surgery from 2012 to 2014 were determined with the Mini-Mental State Examination, and patients with scores under 24 were diagnosed with CI. The patients were then divided into a CI group (n=49) and non-cognitive impairment (NCI) group (n=80). RESULTS: Among the 129 patients, 49 (38.0%) were diagnosed with CI, and 9 (7.0%) had severe CI. The age of the CI group (72.88±6.20 years) was significantly greater than that of the NCI group (69.96±4.53 years). In contrast, the postoperative visual analog scale scores and performance statuses did not differ significantly. However, postoperative delirium was more frequent and the hospital stay length was longer in the CI group compared with the NCI group (p<0.05). CONCLUSION: A high prevalence of undiagnosed CI was discovered among elderly patients undergoing spine surgery. The existence of CI was associated with higher rates of postoperative delirium and prolonged hospital stays, which affected clinical outcomes. Thus, CI assessments should be included in preoperative evaluations of elderly patients prior to spine surgery.